Interactive multimedia satellite access communications. - Le-Ngoc, Tho (IEEE Communications magazine)
Recent advances in satellite technology are making possible the development of broadband satellite access (BSA) systems for two-way access to multimedia Internet services. This article provides an overview of BSA systems with an emphasis on resource management and interworking techniques to support IP-based multimedia services. The article draws on collaborative research performed over the past few years as part of the Broadband Satellite Communications Major Project of the Canadian Institute of Telecommunications Research. Some key innovations are described: combined free/demand assigned multiple access (CFDAMA) for dynamic satellite bandwidth allocation; an architecture for DiffServ provisioning over BSA systems; and a dynamic TCP Vegas protocol as a proxy service for split-TCP connections over BSA systems.